2011
DOI: 10.1021/la201727t
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Adhesion Force by Means of Nanoscale Surface Roughness

Abstract: Control of adhesion is a crucial aspect in the design of microelectromechanical and nanoelectromechanical devices. To understand the dependence of adhesion on nanometer-scale surface roughness, a roughness gradient has been employed. Monomodal roughness gradients were fabricated by means of silica nanoparticles (diameter ∼12 nm) to produce substrates with varying nanoparticle density. Pull-off force measurements on the gradients were performed using (polyethylene) colloidal-probe microscopy under perfluorodeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
88
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 31 publications
(42 reference statements)
7
88
1
Order By: Relevance
“…It is usually assumed that the process takes place in a regime of small strains, that the materials are homogeneous, isotropic, linearly elastic, and that the tips are perfectly smooth. On this last point, previous studies [68] have demonstrated the high sensitivity of adhesion to interfacial roughness showing a drop in F adh of more than an order of magnitude with increasing roughness, down to the atomic limit [9]. …”
Section: Introductionmentioning
confidence: 96%
“…It is usually assumed that the process takes place in a regime of small strains, that the materials are homogeneous, isotropic, linearly elastic, and that the tips are perfectly smooth. On this last point, previous studies [68] have demonstrated the high sensitivity of adhesion to interfacial roughness showing a drop in F adh of more than an order of magnitude with increasing roughness, down to the atomic limit [9]. …”
Section: Introductionmentioning
confidence: 96%
“…Also the changes of the mechanical properties at nanoscale were reported as the result of the environmental conditions [3,7] or local, nanoscale wear [16]. It should be emphasized, that the issue of the mechanical non-homogeneity must be also carefully analyzed, in particular while the sample is used as the stiffness/ Young modulus reference material [17] or the adhesion phenomena is investigated [18]. The observation of the changes of the material's properties requires certain approach, which should provide the reliability of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Control of adhesion forces is important particularly in devices that employ M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT microelectromechanical and nanoelectromechanical systems [15], and in non-fouling coatings where a decrease in adhesion forces could significantly reduce the probability of any form of non-specific adsorption. In these cases, the increase in surface roughness was found to be beneficial in reducing adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the increase in surface roughness was found to be beneficial in reducing adhesion. Various strategies have therefore been developed to increase the nanoscale roughness including the deposition of nanoparticles [15,16] and inorganic films [17] as well as the control of surface morphology by means of polymer coatings [18].…”
Section: Introductionmentioning
confidence: 99%